Research on formulation optimization and hydration mechanism of phosphogypsum-based filling cementitious materials - Yang, Xiao; Jia, Yongxiang; Yang, Chen; He, Xiaoke; Jia, Yanchang; Xu, Leige (Frontiers in Environmental Science, 2022)
Phosphogypsum is a solid waste produced in the wet phosphoric acid process. The main component is calcium sulfate dihydrate, and its activity is very low. It is a very difficult waste to handle. The slag produced in the ironmaking process of Jiuquan Iron and Steel Company has high activity and can be mixed with phosphogypsum to prepare backfilling cementitious materials for backfilling the goaf to prevent subsidence, cracking and subsidence of the surface above the goaf. In this paper, the orthogonal test of material strength under different ratios and finenesses was carried out, and the optimal formula of phosphogypsum-based cementitious material was obtained. On this basis, SEM (Scanning Electron Microscope) and XRD (X-ray Diffraction) were used to observe the internal structure of phosphogypsum-based cementitious materials. The results show that: when the content of quicklime is 5.5%-6.0%, the content of phosphogypsum is 30%-33%, the content of NaOH is 1.5%-2.0%, the content of Glauber's salt is 2.5%-3%, the average particle size is 15.88um, the grinding aid and early In the case of the strong agent, the 3-day and 7-day strengths of the filling reached the highest values ​​of 1.58 MPa and 4.1 MPa, respectively. The formation of calcium silicate hydrate gel (C-S-H) and ettringite (AFt) gradually increased with age, and the structure became denser. The ettringite plays a role of interspersed support in the filling body, thereby improving the overall strength. This research provides theoretical basis and practical reference for the treatment of goaf.